Effect of Clostridium perfringens type C on TLR4/MyD88/NF-κB signaling pathway in piglet small intestines. (October 2019) - Shi, Hairen; Huang, Xiaoyu; Yan, Zunqiang; Yang, Qiaoli; Wang, Pengfei; Li, Shenggui; Sun, Wenyang; Gun, Shuangbao
Abstract: Clostridium perfringens ( C. perfringens ), a Gram-positive bacterium, is one of the main causing piglet diarrhea, which leads serious economic loss in the world swine industries. Generally, the innate immune response plays a critical role in host defense against pathogen invasion. TLR4, a member of the TLR (Toll-like receptor) family, has been considered to implicate in the host immune responses and induce secretion of inflammatory cytokines during bacterial infection. However, little is clear about the effects of TLR4 and key signaling genes in the process of piglet inflammatory and immune responses after C. perfringens infection. This study aims to explore the effect of C. perfringens type C infection on the key mRNAs of TLR4/MyD88/NF-κB signaling pathways during the process of piglet diarrhea. In this study, the expressions of TLR4 and other key mRNAs in the TLR4/MyD88/NF-κB signaling pathways were quantified in piglet ileum and jejunum tissues among IR (intestinal resistance), IS (intestinal susceptibility) and IC (intestinal control) groups by qPCR and Western blot methods, the concentrations of pro-inflammatory cytokines in intestinal tissues and serum immunoglobulins were also tested by ELISA kits. Results showed that compared to IC group, expressions of ileum TLR4 and TNF-α was significantly increased in the IS and IR groups, specially TBK1 gene; the expressions of ileum TLR2, TRAF6, MyD88 and IL- 8 mRNAs was significantly up-regulated in the IS group, the expressions of TLR9, NF-κB, IL-6, IFN-γ and MAPK1 genes were not significant differences among the IR, IS and IC groups. Meanwhile, the protein levels of TLR4, HMGB1 and NF-κB were higher in the IS and IR groups. The levels of jejunum IFN-γ and IL-6, ileum IL-6 and IL-12 were risen in the IR group. Serum immunoglobulin IgA and IgG in the IR and IS groups reached a peak on the 72 h and 48 h post infection, respectively. These findings suggest that C. perfringens type C infection induces host immune responses involving in the TLR4/MyD88/NF-κB signaling pathways in ileum than in jejunum, which may provide valuable information for innate immune mechanisms involved in regulation of piglet diarrhea caused by C. perfringens type C infection. Highlights: Clostridium perfringens infection in pigs was studied in detail for the first time, In molecular biology and signaling pathways. C. perfringens type C can lead to the disregulatory expressions of intestinal TLR mRNAs and downstream associated inflammatory factors, meanwhile it can improve production of cytokines to endorse the mucosal immunity, especially in jejunum. This will be helpful for the study of intestinal immunity of piglets.